2009
DOI: 10.4238/vol8-2kerr012
|View full text |Cite
|
Sign up to set email alerts
|

Cuticular hydrocarbons in the stingless bee Schwarziana quadripunctata (Hymenoptera, Apidae, Meliponini): differences between colonies, castes and age

Abstract: T.M. Nunes et al. lyzed. There were significant differences between bees from different colonies, workers of different age and between workers and virgin queens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 21 publications
3
23
0
3
Order By: Relevance
“…According to these authors, the foragers contain a greater variety of cuticular compounds that assist in the recognition of nest mates. However, the results found by us are in agreement with other studies on stingless bees (Abdalla et al, 2003;Nunes et al, 2009b;Ferreira-Caliman et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…According to these authors, the foragers contain a greater variety of cuticular compounds that assist in the recognition of nest mates. However, the results found by us are in agreement with other studies on stingless bees (Abdalla et al, 2003;Nunes et al, 2009b;Ferreira-Caliman et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…Studies on chemical signaling have shown that the profiles of cuticular hydrocarbons can be used in the recognition among nestmates due to its colonyspecific composition in ants (Bonavita-Cougourdan et al, 1987;Vander Meer et al, 1989;Wagner et al, 2000;Sturgis & Gordon, 2011;Wilgenburg et al, 2011), bees (Breed & Stiller, 1992;Breed et al, 1995;Breed et al, 1998;Dani et al, 2005;Nunes et al, 2008;Nunes et al, 2009;Nunes et al, 2011), wasps (Pfenning et al, 1983;BonavitaCourgoudan et al, 1991;Gamboa et al, 1996;Dani et al, 2001;Tannure-Nascimento et al, 2007;Bruschini et al, 2011;Mitra et al, 2014) and termites (Haverty & Thorne, 1989;Bagnères et al, 1991;Kaib et al, 2002;Kaib et al, 2004. In independent founding wasps, cuticular hydrocarbons have been mainly studied in the subfamilies Polistinae (in Polistes) and Stenogastrinae. On the other hand, few studies have investigated the chemical communication in genus Ropalidia and Mischocyttarus.…”
mentioning
confidence: 99%
“…The results from this reflectance-based study underscore the potential of hyperspectral imaging of the insect body as an approach to nondestructively and noninvasively quantify stress detection. The role of epicuticular hydrocarbons in both intra-and interspecific communication among insects is well established (50), as they tend to vary (a) among closely related species (33,119), (b) in relative (40) or actual (51) composition among males and females within a species, (c) among life stages and age of adults (14,49,70,119,159), (d ) among eusocial individuals with different tasks (38,104), (e) according to mating behavior and status (49,51,129), and ( f ) in response to environmental conditions (27,49,51). Owing to the intra-and interspecific variations in epicuticular hydrocarbon profiles, it seems reasonable to assume that reflectance profiles acquired from insect surfaces may be used to study physiological responses by insects and quantify differences among species.…”
Section: Insect Physiology and Phenomicsmentioning
confidence: 99%